2013
DOI: 10.1177/1721727x1301100314
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of the Toll-like Receptor 2 Agonists, PGN and PAM3CSK4, on Substance P-Induced Human Mast Cell Activation

Abstract: Mast cells play important roles in innate immunity through their activation via toll-like receptors (TLRs) but also contribute to neuroimmunological responses and inflammation through their activation by the neuropeptide substance P (SP) via Ga ilo proteins. This study aims to compare the effects of the TLR2 agonists peptidoglycan (PGN) and tripalmitoyl-S-glycero-Cys-(Lys)4 (Pam3CSK4) on SP-induced human mast cell activation. The human mast cell line LAD2 was employed and mast cell activation was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“…Furthermore, 24 h pre-incubation of PGN and Pam3CSK4 inhibited anti-IgE induced calcium mobilization in LAD2 cells, which was a necessary upstream signaling mechanism required for antigen induced mast cells degranulation [15] . In contrast to our previous study which observed that only Pam3CSK4 but not PGN could suppress calcium increase induced by the neuropeptide, substance P [24] , the inhibitory action of PGN against anti-IgE induced calcium increase suggested that Pam3CSK4 and PGN modulate different sources of calcium. Since substance P induces mainly release of calcium from intracellular stores while FcεRI activation induces calcium influx through opening of cell membrane calcium channels, the activation of TLR2/6 heterodimer by PGN may thus suppress the functions of calcium channels.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 24 h pre-incubation of PGN and Pam3CSK4 inhibited anti-IgE induced calcium mobilization in LAD2 cells, which was a necessary upstream signaling mechanism required for antigen induced mast cells degranulation [15] . In contrast to our previous study which observed that only Pam3CSK4 but not PGN could suppress calcium increase induced by the neuropeptide, substance P [24] , the inhibitory action of PGN against anti-IgE induced calcium increase suggested that Pam3CSK4 and PGN modulate different sources of calcium. Since substance P induces mainly release of calcium from intracellular stores while FcεRI activation induces calcium influx through opening of cell membrane calcium channels, the activation of TLR2/6 heterodimer by PGN may thus suppress the functions of calcium channels.…”
Section: Discussioncontrasting
confidence: 99%
“…Previously, we have demonstrated that PGN and Pam3CSK4 induced the release of IL-8 by employing different signaling pathways in LAD2 cells. Furthermore, activation of different signaling pathways induced by PGN and Pam3CSK4 also resulted in opposite modulatory effect on LAD2 cells activation in response to substance P [24] . In the current study, Pam3CSK4 but not PGN acted in synergy with anti-IgE for IL-8 release from LAD2 cells which is the reverse of the modulatory actions of the two TLR2 agonists on substance P activated LAD2 cells.…”
Section: Discussionmentioning
confidence: 93%
“…Together with our previous study (Yu et al, 2013), these studies demonstrate the differential function of G o and G i protein in human mast cells.…”
mentioning
confidence: 51%
“…Our previous study has demonstrated that substance P-induced degranulation and release of IL-8 from the human mast cell line LAD2 cells were both blocked by PTX, whereas BAC differentially inhibited degranulation but potentiated IL-8 release (Yu et al, 2013).These results strongly indicate that G i and G o could differentially regulate the activities of human mast cells.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation